Факторы развития местного самоуправления. Оценка значения изоляции и изоляционизма - Плюснин, Юрий (Вопросы государственного и муниципального управления, 2008)
The relationship between the development of local self-governance and their exclusion in modern Russia had found the research of municipal management organization. The hypothesis of local self-government development determination by factors of isolation and isolationism was proposed. The higher the isolation, the higher the level of local government and vice versa. Isolation promotes isolationism as a result of the factors limiting the development of local self-government. Types of isolation – territorial, population and resource. The meaning of isolated forms for the practice of municipal government and its effectiveness has been investigated. When combined three types of isolation has always recorded the unique history and development of local self-governing society. Five key factors for the development of municipalities was identified. Those are a natural (population and territory), resources (natural and financial resources) and management factors. Such factors limit the establishment and development of local self-government. The value of sharp increases in isolation of society and in a situation of isolationism. The development of local self-government in the face of limited resources is accompanied by increased isolation and isolationism, and contrary to the purposes of public policy, especially its distribution and monitoring functions. It can be one of the major causes of lack of real self-government.